A Low-Frequency Sound Absorption Device Fitting for Power Transformation and Distribution Room. Issue 1 (January 2021) - Wu, Xiaowen; Lu, Ling; Xie, Ziyin; Kim, Hakbong
Abstract: Aiming at the low-frequency noise in power transformation and distribution rooms in residential areas, a sound absorption device which can effectively reduce the low-frequency noise of 100 Hz was proposed. Through an efficient and integrated design, the resonance frequency of the device, the frequency of bending vibration from S-shaped tubes when anastomosis effects ocurred, the frequency of Helmholtz resonant cavities in the S-shaped tubes, and the frequency of the slit resonant sound-absorbing structure consisting of the splits between S-shaped tubes and the cavity behind them were all designed at 100 Hz. Thus, the sound energy of 100 Hz in the power transformation and distribution rooms could be absorbed efficiently. Through sound field simulation, the acoustical performance of S-shaped tubes was further analyzed, and the wave peak of S-shaped tube was optimized to effectively enhance the sound absorption coefficient. The results showed that the device of sound absorption had a good acoustical performance.